Diagenetic Process and Their Effect on Reservoir Quality in Miocene Carbonate Reservoir, Offshore, Sarawak, Malaysia - Hammad Tariq Janjuhah, Ahmed Mohammad Ahmed Salim, Deva Parsed G, . (2017)
he carbonate platforms form one of the genetic gas reservoirs in the subsurface in Central Luconia, offshore, Sarawak, Malaysia. A detailed investigation of available core and thin sections revealed that different diagenetic parameters influence the reservoir quality in Central Luconia.